The Effect of Lapbook Learning Media on The Science Learning Outcomes Of Grade IV - Nita Dila; Lisbet Novianti Sihombing; Minar T. Lumbantobing (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This research was conducted in class IV at state elementary school 122371Pematangsiantar 2025/2026 academic year which began with an observation on June 20, 2025 and continued with the implementation of the pretest on August 28, 2025, the pretest results showed that only 3 students were able to achieve the completion criteria before being given treatment. Based on the pretest results, the average student learning outcomes were 49.12 with 3 students completing, this was due to the different knowledge and abilities of students. In addition, the pretest questions that were prepared had also been adjusted to the characteristics of the abilities of high-class students. By looking at the pretest results, it can be said that learning that has not used the lapbook learning media is still not successful or very low. Then, the average value obtained from the posttest results was 85.12 so after using the lapbook media, the learning outcomes obtained were higher compared to before using the lapbook learning media Based on the results of the normality test used to determine whether the data is normally distributed or not. So the results obtained are normally distributed because the pretest results are 0.129005 and posttest 0.152 0.05, so the posttest results have increased. Then in the hypothesis test the results of the unpaired sample test analysis were obtained, namely 13.416 2.064. This means that there is an influence of taptook learning media on the science learning outcomes of grade IV students of UPTO SD Negeri 122371 Pamatangsiantar, so Ho is rejected and Ha is accepted.